2021
DOI: 10.2147/ijnrd.s334024
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatments from Inhibition of the Intestinal Sodium–Hydrogen Exchanger 3

Abstract: Plasma membrane sodium–hydrogen exchangers (NHE) transport Na + into cells in exchange for H + . While there are nine isoforms of NHE in humans, this review focuses on the NHE3 isoform, which is abundantly expressed in the gastrointestinal tract, where it plays a key role in acid–base balance and water homeostasis. NHE3 inhibition in the small intestine results in luminal sodium and water retention, leading to a general decrease in paracellular water flux and diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Against this background, we have hypothesized that therapeutically targeting NHE3 may present us a new additional pathway to treat human hypertension. As proof-of-concept studies, gastrointestinal NHE3 inhibitors have been developed to treat several disease targets including hypertension, constipation, and hyperphosphatemia in elder patients ( Linz et al, 2012 , 2016 , 2020 ; Li et al, 2019b ; Kovesdy et al, 2021 ). One NHE3 blocker, SAR218034 (SAR), has been shown to increase fecal sodium excretion and decrease systolic blood pressure in lean old SHRs ( Linz et al, 2012 ).…”
Section: Perspectives On Therapeutically Targeting Intestinal and Kid...mentioning
confidence: 99%
“…Against this background, we have hypothesized that therapeutically targeting NHE3 may present us a new additional pathway to treat human hypertension. As proof-of-concept studies, gastrointestinal NHE3 inhibitors have been developed to treat several disease targets including hypertension, constipation, and hyperphosphatemia in elder patients ( Linz et al, 2012 , 2016 , 2020 ; Li et al, 2019b ; Kovesdy et al, 2021 ). One NHE3 blocker, SAR218034 (SAR), has been shown to increase fecal sodium excretion and decrease systolic blood pressure in lean old SHRs ( Linz et al, 2012 ).…”
Section: Perspectives On Therapeutically Targeting Intestinal and Kid...mentioning
confidence: 99%
“…Because intestinal absorption of water depends on the presence of sodium in the intestinal lumen, restriction of sodium may also play a role in determining a negative water balance 36 . Thus, salt restriction may facilitate water reabsorption from the stool in the rectum, leading to dry and hard stools, impeding peristalsis, and resulting in a decrease in bowel movement frequency 37 . Constipation may be an important risk factor for anorexia 38,39 and impaired functional status in older adults, 40,41 both of which relate to decreased muscle mass and strength, 42,43 which can cause falls 44 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Thus, salt restriction may facilitate water reabsorption from the stool in the rectum, leading to dry and hard stools, impeding peristalsis, and resulting in a decrease in bowel movement frequency. 37 Constipation may be an important risk factor for anorexia 38,39 and impaired functional status in older adults, 40,41 both of which relate to decreased muscle mass and strength, 42,43 which can cause falls. 44 Sodium is also essential for the formation of action potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Independently of the above-mentioned coupling with di-/tripeptide absorption, NHE3 activity represents the major mechanism of intestinal Na + absorption accompanied by mostly paracellular water uptake ( Karasov, 2017 ). It thus contributes significantly to body fluid and blood pressure homeostasis as well as acid-base regulation ( Pedersen and Counillon, 2019 ; Kovesdy et al, 2021 ; Zhuo et al, 2021 ) which is supported by a number of studies using elaborate NHE3 knockout mouse models, such as tissue-specific ( Dominguez Rieg et al, 2016 ) or tamoxifen-inducible intestinal epithelial cell-specific NHE3 knockout mice ( Xue et al, 2020 ), or specific drugs such as the first-in-class NHE3 inhibitor tenapanor ( Spencer et al, 2014 ; Yu et al, 2019 ; Zhou et al, 2021 ). Treating NHE2 knockout mice with tenapanor revealed that NHE2 contributes to colonic fluid absorption only marginally, if at all ( Nikolovska et al, 2022 ).…”
Section: Nhe3 In the Gastrointestinal Tractmentioning
confidence: 99%
“…Trafficking between plasma membrane and compartments is a common method of acute regulation. As for NHE3, trafficking represents a temporary compartmentalization of transport activity, i.e., NHE3 remains active in recycling endosomes ( D'Souza et al, 1998 ; Kovesdy et al, 2021 ). In addition to a constitutively recycling NHE3 population, another intracellular population seems to be located in storage compartments, potentially waiting to be recruited to the cell surface when acutely needed, e.g., in order to reabsorb Na + in proximal renal tubules ( Alexander et al, 2005 ; Alexander and Grinstein, 2009 ).…”
Section: Nhe3 In the Gastrointestinal Tractmentioning
confidence: 99%